Star Power: Early life stages of an endangered sea star are robust to current and near-future warming - Jason Hodin; Fleur P. Anteau; Brook F. Ashcraft; Michael Brito; Fiona Curliss; Augustin R. Kalytiak-Davis; James S. Peng; Chloe J. Schwab; Vannessa V. Valdez; Willem Weertman (PLoS ONE, 2025)
The sunflower star, Pycnopodia helianthoides , was a top benthic predator throughout its former range from Alaska to northern Mexico, until its populations were devastated starting in 2013 by a disease known as seastar wasting. The subsequent absence of sunflower stars from northern California waters was coincident with a dramatic ecological phase shift from healthy bull kelp forests ( Nereocystis luetkeana ) to barrens formed by purple sea urchins ( Strongylocentrotus purpuratus ), a prey of sunflower stars. Modeling suggests that restoration and resilience of kelp forests can be enhanced by the return of sunflower stars. Towards this end we run a conservation breeding program for sunflower stars in the Salish Sea of Washington, where sunflower stars have persisted in much reduced numbers. We here report on a variety of investigations into the temperature tolerance of sunflower stars, focusing on their poorly studied early life stages from their planktonic embryos and larvae, through metamorphosis and settlement as they transition to the benthos, and then for eight months of juvenile growth. Our results indicate that the optimum temperature for early life stage sunflower stars is more than 4°C higher than ambient temperatures in the Salish Sea, and that the juveniles demonstrate enhanced performance to a simulated marine heat wave. These results suggest that Salish Sea-derived sunflower stars would be robust to current and even near-future predicted temperatures in the south of their former range.